2017
DOI: 10.1002/14651858.cd008482.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K supplementation for cystic fibrosis

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
4
0
4
Order By: Relevance
“…It has been suggested that exocrine pancreatic insufficiency and malabsorption of fats and bile salts in CF patients can lead to fat-soluble vitamin deficiency, including vitamin K. 14,29,30 Rashid et al, found significantly higher levels of PIVKA-II in CF patients with pancreatic insufficiency without vitamin K supplementation (n= 83) compared with subjects with normal pancreatic function (n= 15). 31 Nicolaidou et al, found significant differences in u-OC (median 4.0 vs. 8.1 ng/ml, p= 0.017) and c-OC concentrations (median 22.0 vs. 13.8 ng/ml, p= 0.002) among healthy individuals (n= 25) and CF patients with pancreatic insufficiency without vitamin K supplementation (n= 20).…”
Section: Clinical Biochemical and Functional Parameters In Cf Patimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that exocrine pancreatic insufficiency and malabsorption of fats and bile salts in CF patients can lead to fat-soluble vitamin deficiency, including vitamin K. 14,29,30 Rashid et al, found significantly higher levels of PIVKA-II in CF patients with pancreatic insufficiency without vitamin K supplementation (n= 83) compared with subjects with normal pancreatic function (n= 15). 31 Nicolaidou et al, found significant differences in u-OC (median 4.0 vs. 8.1 ng/ml, p= 0.017) and c-OC concentrations (median 22.0 vs. 13.8 ng/ml, p= 0.002) among healthy individuals (n= 25) and CF patients with pancreatic insufficiency without vitamin K supplementation (n= 20).…”
Section: Clinical Biochemical and Functional Parameters In Cf Patimentioning
confidence: 99%
“…11,12 Vitamin K deficiency predisposes CF patients to easy bruising and bleeding (especially among infants), defective bone mineralization and osteoporosis. [13][14][15] R o u t i n e v i t a m i n K s u p p l e m e n t a t i o n in CF patients is recommended in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha indicado que la insuficiencia pancreática exocrina y la hipoabsorción de grasas y sales biliares en los pacientes con FQ pueden provocar deficiencia de vitaminas liposolubles, incluida la vitamina K. 14,29,30 Rashid y col. hallaron valores significativamente mayores de PIVKA-II en los pacientes con FQ e insuficiencia pancreática sin suplementación con vitamina K (n= 83) en comparación con los sujetos con función pancrática normal (n= 15). 31 Nicolaidou y col., encontraron diferencias significativas en la OCic (mediana de 4,0 frente a 8,1 ng/ml, p= 0,017) y en la osteocalcina carboxilada (mediana de 22,0 frente a 13,8 ng/ml, p= 0,002) entre los sujetos sanos (n= 25) y los pacientes con FQ e insuficiencia pancreática sin suplementación con vitamina K (n= 20).…”
Section: Tabla 5 Análisis De Regresión Múltiple Escalonada Hacia Adeunclassified
“…33 La hepatopatía también está indicada como uno de los factores de riesgo de deficiencia de vitamina K en los pacientes con FQ. 14 Mosler y col. demostraron concentraciones normales de PIVKA-II solamente en dos de 15 sujetos con FQ con hepatopatía que recibían ácido ursodesoxicólico por vía oral debido a una actividad elevada de la GGT. 13 Rashid y col. y Wilson y col., documentaron concentraciones patológicas de PIVKA-II en todos los pacientes con FQ y hepatopatía (n= 8 y n= 6, respectivamente).…”
Section: Tabla 5 Análisis De Regresión Múltiple Escalonada Hacia Adeunclassified
See 1 more Smart Citation